(untitled) (Observatorio Económico, 2014)
Labor reform—together with tax, constitutional, and education reform—is one of the four pillars of the current government’s program. So the Minister of Labor, Javiera Blanco, has asserted. However, as the last quarter of the year begins, little is known about its details. Moreover, in mid-October, the minister herself reportedly said at a meeting with the Socialist Party’s congressional caucus that this reform will probably be implemented in 2016, when a better economic cycle is expected. The truth is that, regardless of the economy’s cycles, it is imperative to begin discussing what kind of organization we want for the labor market. I will not blindly defend, without access to the fine print, the ideas put forward by the CUT (Central Unitaria de Trabajadores, Chile’s main trade union confederation) and the government, since all we know, in broad terms, is that they aim to “strengthen” union organization. Continue reading...